Balloon kyphoplasty: errors and complications - Borys Pavlov (Ukrainian Neurosurgical Journal, 2016)
Introduction. Percutaneous balloon kyphoplasty was developed for vertebral compression fractures minimally invasive treatment. Subsequently, this technique has been widely and successfully used for traumatic and tumor spine fractures treatment. However, the data complications during manipulation are insufficient in the literature.Goal. Estimate the frequency and nature of intraoperative and postoperative complications during balloon kyphoplasty.Materials and methods. We have studied the results of treatment 63 patients (a total 75 levels of compression), which percutaneous balloon kyphoplasty was performed. We present patients with traumatic and osteoporotic thoracolumbar fractures ages of 19 to 85 years. Women were 35, men were 28.Results and discussion. Neurological and infectious complications did not occur. In 3 cases (4%) was observed paravertebral bone cement leakage, in 1 case (1.3%) intradiscal and 1 case (1.3%) intravascular. The total percentage of complications is comparable with literature data for this operations type. Clinically significant manifestations of these incidents had not.Conclusions. Percutaneous balloon kyphoplasty — a safe method of minimally invasive treatment of thoracolumbar spine fractures. Careful planning and technically correct execution of its by trained staff allows us to reduce complications to a minimum.